The Relationship Between Emotional Regulation and Anxiety Levels in Early Adult Women in Long Distance Marriage - Novia Aira Fitri; Nurmina (Universitas Negeri Medan, 2026)
This study aims to determine the relationship between emotional regulation and anxiety levels in early adult women undergoing long-distance marriage. This study uses a quantitative approach with a correlational design. The research subjects were 155 early adult women undergoing long-distance marriage who were selected using a purposive sampling technique. The instrument used was the Emotion Regulation Questionnaire (ERQ) to measure cognitive reappraisal and expressive suppression strategies, which consists of 10 items with a 7-point Likert scale, and the Depression Anxiety and Stress Scale (DASS) anxiety subscale which consists of 14 items with a 4-point Likert scale. Data analysis was carried out using multiple regression and hypothesis testing was carried out with simultaneous F tests, partial t tests, and coefficient of determination tests. The results showed that emotional regulation was related to anxiety simultaneously by obtaining a sig. value. The F test was 0.003 <0.05, and the partial t test results also showed that cognitive reappraisal strategies had no relationship with anxiety obtained a sig. 0.724 > 0.05 and expressive suppression was found to be related to anxiety obtained a sig. 0.001 <0.05, and the results of the determination coefficient test obtained an R Square value of 0.072. This means that emotional regulation strategies contribute to the anxiety variable with a proportion of 7.2% while the rest is explained by other factors outside the research model. These findings indicate that emotional regulation is an important factor in maintaining psychological well-being in early adult women in long-distance relationships. Therefore, it is important to understand how emotional regulation strategies can be optimized in facing the dynamics of long-distance marriage.